(untitled) (Profetik: Jurnal Komunikasi, 2022)
This research investigates Da’wah activities conducted by women politicians on Facebook, focusing on Intsiawati Ayus, a member of the DPD RI in Indonesia. The study employs qualitative content analysis, utilizing a pragmatic form to classify signs related to Bil-Haal Da’wah and Bit-Tadwin Da’wah. A total of 26 Facebook posts from the influential female politician were analyzed. The findings reveal that women politicians engage in Bil-Haal Da’wah, which showcases exemplary da’wah activities for the community to emulate. Additionally, they conduct Bit-Tadwin Da’wah through written content on social media platforms. These results highlight the significant role of Muslim politicians, with verified Facebook accounts, in carrying out Da’wah activities beyond traditional preachers, providing insights into the communication strategies adopted by women politicians in promoting their political and religious beliefs. The politicians also encourage the audience to refrain from spreading fake news and pray for the deceased. They also advocate for spending time with family, emphasizing the significance of family bonding in Islamic teachings. The research concludes that politicians can effectively carry out da’wah activities through social media, setting examples for the community and fostering a sense of brotherhood and religious commitment among followers.